Catalyst Composition and Content Effects on the Synthesis of Single-Walled Carbon Nanotubes by Arc Discharge. (20th March 2007) - Zhao, Tingkai; Tang, Qinghu; Liu, Yongning; Zhu, Changchun; Zhao, Xiang
Abstract : Single-walled carbon nanotubes (SWCNTs) were prepared by a modified arc discharging furnace using Fe-Ni-Mg powders as catalyst at600 ∘ C . The effects of catalyst composition and content on the production rate and purity of SWCNTs are investigated in this paper. When the Fe-Ni-Mg catalyst composition is 2: 1: 2wt % and the catalyst content is 5wt %, the experimental results indicate that the production of SWCNTs is 12 grams per hour, and the purity and diameter of SWCNTs are70 % and 1.22∼ 1.38 nm, respectively. The results indicate that the cooperative function of catalyst composition and content plays an important role in the production of SWCNTs. The aim of this work is to control the production process of SWCNTs efficiently.